Mechanical properties of computer-aided design/computer-aided manufacturing resin composites assuming perfect silane coupling using in silico homogenization of cryo-electron microscopy images. Issue 1 (January 2019) - Lee, Chunwoo; Yamaguchi, Satoshi; Ohta, Keisuke; Imazato, Satoshi
Abstract: Purpose: The aim of this study was to determine the mechanical properties of computer-aided design/computer-aided manufacturing (CAD/CAM) resin composites for dental restoration assuming perfect silane coupling by in silico homogenization analysis using a three-dimensional model constructed from cryo-electron microscopy (cryo-EM) images. Methods: Three-dimensional dataset of a commercial CAD/CAM resin composite block (RCB) was obtained using EM with cryo-stage and focused ion beam at −130 °C. The region of inspection was 1.8 μm × 1.4 μm × 1.2 μm, and 213 slices were obtained from this region. Each slice was processed (noise reduction, threshold setting, and segmentation) using image processing software to design an in silico model. From the processed image slices, a bulk three-dimensional object and stereolithography model were reconstructed using voxel modeling software. To evaluate the elastic modulus and Poisson's ratio of the CAD/CAM RCB, homogenization analysis was performed. Results: The generated voxel model included 37, 276, 216 voxels, 42, 472, 040 patches of the surface, 2, 123, 672 nodes, a volume of 165, 748, 899, and a surface area of 175, 206, 723. The mean of the elastic moduli along each axis was 10.71 ± 1.79 GPa. The mean of the Poisson's ratios of each plane was 0.23 ± 0.02. Conclusions: A CAD/CAM resin composite model was successfully reconstructed from cryo-EM images, suggesting that the established image processing method is useful for producing dental restorative materials containing nano-fillers and for predicting homogenized mechanical properties. The homogenized mechanical properties indicated that the mechanical properties of the CAD/CAM RCB assumed perfect silane coupling between the fillers and resin matrix.